T cell subsets, regulatory T, regulatory B cells and proinflammatory cytokine profile in Schistosoma haematobium associated bladder cancer: First report from Upper Egypt. - Sara Abdelal Mohammed; Helal F Hetta; Asmaa M Zahran; Mohammed E M Tolba; Rasha A H Attia; Hosny M Behnsawy; Abdelazeem M Algammal; Gaber El-Saber Batiha; Ahmed Qasem Mohammed; Alzahraa Abdelraouf Ahmad (Public Library of Science (PLoS), 2023)
Background The function of different populations of the immune system in bladder cancer (BCa) is well established. However, the cohesive role of the immune cell profile of schistosomal BCa at systemic and tissue levels is still lacking, especially in endemic countries. The balance hypothesized between protumorigenic and antitumor molecules determines the prognosis of tumor progression. This study aimed to investigate the frequency of T cell subsets at both blood and tumor tissue, regulatory T(Treg), regulatory B cells (Breg) and proinflammatory cytokines in S. haematobium-related BCa patients in Egypt. Methodology/principal findings The frequency of T cell subsets at both blood and tumor tissue, regulatory T(Treg), regulatory B cells (Breg) were studied by flow cytometry and proinflammatory cytokines by ELISA in S. haematobium-related BCa patients in Egypt. The results indicated a significant increase in the activity of T-cell populations, particularly CD3+, CD4+, and regulatory T cells (Tregs), and a decrease in cytotoxic CD8+ T cells in the patient group. An increased proportion of CD19+CD24+CD38+ Bregs and proinflammatory cytokines (IL-1β, IL-6, and TNF-α) was also observed. However, T-cell subpopulations in the tumor microenvironment showed a significant reduction in cancer patients compared to controls. Moreover, positive correlations were observed between the frequencies of Bregs and Tregs, suggesting the promotion of cancer progression besides their relation to the intensity of schistosomal infection. Conclusions/significance Trapped Schistosoma haematobium eggs in bladder tissue might lead to persistent inflammation that contributes to immunomodulation and promotes tumor progression, as evidenced by the increase in peripheral T helper, Tregs, Bregs and serum tumor-promoting cytokines. Considering the role and integrated functions of specific immune responses in BCa could help future diagnostic and therapeutic implications.